Visual Snippets: Summarizing Web Pages for Search and Revisitation - Teevan, Jaime; Cutrell, Ed; Fisher, Danyel; Drucker, Steven; Ramos, Gonzalo; Andre, Paul; Hu, Chang (Proceedings of CHI 2009, 2009)
People regularly interact with different representations of Web pages. A person looking for new information may initially find a Web page represented as a short snippet rendered by a search engine. When he wants to return to the same page the next day, the page may instead be represented by a link in his browser history. Previous research has explored how to best represent Web pages in support of specific task types, but, as we find in this paper, consistency in representation across tasks is also important. We explore how different representations are used in a variety of contexts and present a compact representation that supports both the identification of new, relevant Web pages and the re-finding of previously viewed pages.